MENGOPTIMALKAN PLATFORM DIGITAL DALAM MENDORONG SEMANGAT BELAJAR - Mareike Seska Diana Lotulung; Juwinner Dedy Kasingku (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information and communication technology has changed how people, especially adolescents and university students, access information, communicate, and express themselves. Social media has become a primary platform widely used by students for entertainment, information, and communication. This study employed a qualitative method with a phenomenological approach to examine the influence of social media on the learning motivation of students at a private university in Manado in the 2024/2025 academic year. Data were collected through interviews with 30 active students who regularly use social media, supported by a literature review. The results show that WhatsApp, TikTok, and Instagram are the most frequently used platforms, mainly for entertainment, information, and communication purposes. In addition, social media has been shown to support learning motivation through educational content, social interaction, and digital rewards, although the duration of use needs to be managed to prevent health problems and addiction. In conclusion, social media not only facilitates communication and access to information but also serves as an effective tool to support the learning process, stimulate curiosity, and enhance students’ motivation to learn in the digital era.